2015
DOI: 10.1002/jsfa.7062
|View full text |Cite
|
Sign up to set email alerts
|

Composition and biological activities of slaughterhouse blood from red deer, sheep, pig and cattle

Abstract: Fractionated animal blood obtained from local slaughterhouses contains native proteins that possess antioxidant activity and antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 39 publications
(85 reference statements)
3
25
0
Order By: Relevance
“…Other proteins identified were creatine kinase (CKM) in two spots (spots 6 and 30) in the range from 30 to 50 kDa and serum albumin (ALB; spots 19, 20 and 21). In the case of ALB, the highest spot volumes found in control samples (18.33, 8.89 and 20.62; Table 2) might result from vascular tissue and blood included in the muscle sample, since ALB is present in sheep blood at high concentrations (25.3 g L À1 ; Bah et al (2016)). This proteomic study also revealed other proteins, such as ATP synthase subunit alpha 2 (ATPAF2), cytochrome (QCRC), heat shock 70 kDa (HSP70), malate dehydrogenase (MDH1), glycogen phosphorylase (PYGM), aldehyde dehydrogenase (ALDH2) and retinal dehydrogenase (ALDH1A1).…”
Section: Resultsmentioning
confidence: 99%
“…Other proteins identified were creatine kinase (CKM) in two spots (spots 6 and 30) in the range from 30 to 50 kDa and serum albumin (ALB; spots 19, 20 and 21). In the case of ALB, the highest spot volumes found in control samples (18.33, 8.89 and 20.62; Table 2) might result from vascular tissue and blood included in the muscle sample, since ALB is present in sheep blood at high concentrations (25.3 g L À1 ; Bah et al (2016)). This proteomic study also revealed other proteins, such as ATP synthase subunit alpha 2 (ATPAF2), cytochrome (QCRC), heat shock 70 kDa (HSP70), malate dehydrogenase (MDH1), glycogen phosphorylase (PYGM), aldehyde dehydrogenase (ALDH2) and retinal dehydrogenase (ALDH1A1).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, many cultures also consume blood as food or in combination with meat and other ingredients such as in blood sausage, black puddings and pancakes [62]. In feed industry, blood is used in the production of blood meal for feeding livestock and pets [18,65]. In medicine, blood is usually processed and used as a medium for the growth of probiotic bacteria (bovine plasma), the raw material for pharmaceutical porphyrin derivative production, a precursor to thrombin production and purification, the active ingredient in topical surgical hemostatic applications, and a reagent for routine blood clotting in serology laboratories [65].…”
Section: Utilization Of Inedible By-productsmentioning
confidence: 99%
“…In feed industry, blood is used in the production of blood meal for feeding livestock and pets [18,65]. In medicine, blood is usually processed and used as a medium for the growth of probiotic bacteria (bovine plasma), the raw material for pharmaceutical porphyrin derivative production, a precursor to thrombin production and purification, the active ingredient in topical surgical hemostatic applications, and a reagent for routine blood clotting in serology laboratories [65]. When blood is collected from any animal, it is compulsory that such animal should be free from disease before the blood can be consumed or processed into food.…”
Section: Utilization Of Inedible By-productsmentioning
confidence: 99%
“…The red cells of non‐mammalian vertebrates, such as poultry species, also contain a nucleus . Plasma is an aqueous solution of many substances, predominantly the proteins serum albumin, various globulins and fibrinogen …”
Section: Introductionmentioning
confidence: 99%